2005
DOI: 10.1002/zoo.20053
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral indices of estrus in a group of captive African elephants (Loxodonta africana)

Abstract: This study investigated behavioral signals of estrus by systematically monitoring the interactions of one male with four female African elephants housed in a naturalistic outdoor enclosure at Disney's Animal Kingdom over a period of 11 months. We measured changes in five spatial behaviors and 22 tactile-contact behaviors, as well as changes in serum progestagen and LH concentrations, across three ovarian cycles for each female. Two females did not cycle during the study. Three different phases of the ovarian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Behaviors such as the estrous walk and interest by males appear only days before consort establishment or require the presence of a male [Moss, 1983;Ortolani et al, 2005]. Determining female reproductive state in a noninvasive manner well in advance of mating would be a valuable tool for studies on communication and sexual selection.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviors such as the estrous walk and interest by males appear only days before consort establishment or require the presence of a male [Moss, 1983;Ortolani et al, 2005]. Determining female reproductive state in a noninvasive manner well in advance of mating would be a valuable tool for studies on communication and sexual selection.…”
Section: Discussionmentioning
confidence: 99%
“…Males may monitor their auditory environment for these preovulatory ''estrous rumbles,'' which attract them to groups containing cycling females. Once present, males can switch to other sensory modalities, such as olfaction, to test for current fertility [Rasmussen and Schulte, 1998;Ortolani et al, 2005]. In addition, females may also rumble at this stage to incite male-male competition [Poole, 1989].…”
Section: Mate Attraction Calls and Mating Strategymentioning
confidence: 99%
“…In the female African elephant (Loxodonta africana), estrous cycle length is reported to range between 13 to 17 weeks [17][18][19][20][21][22][23][24][25]. The cycle is divided into a 4 to 6 week follicular phase after 4 which an increase in progesterone levels, believed to trigger ovulation, marks the onset of an 8 to 11 week luteal phase [17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, Delsink et al [11,16] found no significant change in core and total range use, matriarchal status, cow/calf interaction, herd fragmentation/isolation, musth occurrence, bull hierarchy, and no aberrant or unusual behaviour witnessed among the herds. Furthermore, concerns were raised as to the potential effect of the pZP vaccine on luteal function, but to date, there has been no attempt to examine endocrine correlates associated with pZP vaccine use in African elephants.In the female African elephant (Loxodonta africana), estrous cycle length is reported to range between 13 to 17 weeks [17][18][19][20][21][22][23][24][25]. The cycle is divided into a 4 to 6 week follicular phase after 4 which an increase in progesterone levels, believed to trigger ovulation, marks the onset of an 8 to 11 week luteal phase [17,[20][21][22].…”
mentioning
confidence: 99%
See 1 more Smart Citation